1999
DOI: 10.1523/jneurosci.19-19-08182.1999
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Mechanisms of Glial Scarring and Progressive Cavitation:In VivoandIn VitroAnalysis of Inflammation-Induced Secondary Injury after CNS Trauma

Abstract: Post-traumatic cystic cavitation, in which the size and severity of a CNS injury progress from a small area of direct trauma to a greatly enlarged secondary injury surrounded by glial scar tissue, is a poorly understood complication of damage to the brain and spinal cord. Using minimally invasive techniques to avoid primary physical injury, this study demonstrates in vivo that inflammatory processes alone initiate a cascade of secondary tissue damage, progressive cavitation, and glial scarring in the CNS. An i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
351
0
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 503 publications
(366 citation statements)
references
References 83 publications
10
351
0
5
Order By: Relevance
“…Some have suggested that degenerating axons and their dying terminals may be a trigger for such extracellular matrix production by astrocytes (see Massey, et al, in this issue). Evidence also suggests that the inflammatory infiltration and activation associated with CNS injury is associated with production of inhibitory molecules, as CSPGs are associated with breakdown of the blood brain barrier and infiltrating macrophages present within a lesion site (Fitch, et al, 1999;Fitch and Silver, 1997a), a phenomenon that is also seen with activation of oligodendrocyte precursor cells after injury (Rhodes, et al, 2006). Pro-inflammatory molecules that activate microglial cells and macrophages can trigger astrocyte gliosis and upregulation of proteoglycans (Fitch, et al, 1999), upregulation of NG2 proteoglycan by oligodendrocyte precursor cells (Rhodes, et al, 2006), and cytokines associated with inflammation can also influence astrocyte extracellular matrix production (DiProspero et al, 1997).…”
Section: Triggers For the Production Of Inhibitory Extracellular Matrixmentioning
confidence: 99%
See 2 more Smart Citations
“…Some have suggested that degenerating axons and their dying terminals may be a trigger for such extracellular matrix production by astrocytes (see Massey, et al, in this issue). Evidence also suggests that the inflammatory infiltration and activation associated with CNS injury is associated with production of inhibitory molecules, as CSPGs are associated with breakdown of the blood brain barrier and infiltrating macrophages present within a lesion site (Fitch, et al, 1999;Fitch and Silver, 1997a), a phenomenon that is also seen with activation of oligodendrocyte precursor cells after injury (Rhodes, et al, 2006). Pro-inflammatory molecules that activate microglial cells and macrophages can trigger astrocyte gliosis and upregulation of proteoglycans (Fitch, et al, 1999), upregulation of NG2 proteoglycan by oligodendrocyte precursor cells (Rhodes, et al, 2006), and cytokines associated with inflammation can also influence astrocyte extracellular matrix production (DiProspero et al, 1997).…”
Section: Triggers For the Production Of Inhibitory Extracellular Matrixmentioning
confidence: 99%
“…Microglial cells from the CNS and activated macrophages from the periphery both respond to trauma in the brain and spinal cord, and this inflammatory response may contribute to secondary tissue damage after the primary insult (Blight, 1994;Fitch, et al, 1999). This cascade of secondary damage, progressive cavitation, and glial scarring was demonstrated in an in vivo model of inflammation using microinjection of zymosan, a non-toxic, specific phagocytic activator of the macrophage mannose receptor and the beta-glucan site of the CR3 integrin receptor (Fitch, et al, 1999). The resulting inflammation leads to significant axotomy and increases in astrocyte cavity size, while control injections of latex microspheres do not induce this damaging inflammatory cascade.…”
Section: Triggers For the Production Of Inhibitory Extracellular Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] The nontraumatic injection of the micgroglia/macrophage activator zymosan into the brain and spinal cord results in cavitation, demyelination, and axonal injury. 15,16 The molecules released by mature phagocytes, including superoxide, hydrogen peroxide, hypochlorous acid, as well as neurotoxic chemokines and cytokines may be partially responsible for axonal damage and retraction, and neuronal death. 17 The second-generation tetracycline derivative, minocycline, has been shown to be an antiinflammatory agent.…”
Section: Neuroprotection In the Setting Of Scimentioning
confidence: 99%
“…They further showed in a culture model that progressive cavitation could be prevented by treatment with anti-in¯ammatory agents which inhibited macrophage in¯ammatory gene transcription. 44 Further evidence for the detrimental role of neutrophils and macrophages is that reactive oxygen species are produced during the process of phagocytosis by these cells. 45 Thus, neutrophil in¯ux in a SCI has been associated with oxidative damage of surrounding healthy tissue.…”
Section: In¯ammatory Responsesmentioning
confidence: 99%